Identification of Green Competency Needs in Vocational Education Curriculum Development based on Simple Additive Weighting - Latif, Muh Abdul; Widiaty, Isma; Abdullah, Ade Gafar (Graduate School of Universitas Negeri Malang, 2024)
The issue of global environmental sustainability has encouraged the transformation of vocational education to integrate green competencies that are relevant to the needs of the green industry. This research aims to identify the need for green competencies in vocational education curriculum development using the Simple Additive Weighting (SAW) method. This method allows ranking competency elements based on their level of importance in supporting sustainability-oriented learning. The research was conducted through data collection from literature, surveys of stakeholders (teachers, students, and industry). Data collection was conducted online through google form and 1022 respondents participated in this research. The identification results show that the aspects of abilities and skills are aspects that are widely responded by stakeholders such as; being able to provide solutions to environmental problems, being able to take responsibility for environmental sustainability, and communication skills are the main needs that need to be integrated in the curriculum. The resulting recommendations are expected to be a reference in designing a sustainability-based vocational curriculum that not only meets the needs of the labor market but also supports environmental conservation.